Pelaksanaan Simpan Pinjam Pada Usaha Ekonomi Desa Simpan Pinjam (Ued-Sp) Kembang Serumpun Untuk Meningkatkan Perekonomian Masyarakat Desa Banjar Guntung (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The Village-Savings and Loans Economic Business, hereinafter referred to as UED-SP, is aVillage Empowerment Program (PPD) created by the central government to improve the economy of ruralcommunities. The legal basis for UED-SP is regulated in Domestic Government Regulation Number 6 of1998 concerning Village-Savings and Loans Economic Enterprises. The Minister of Home AffairsRegulation Number 6 of 1998 concerning Village-Savings and Loans Economic Businesses gives theunderstanding that UED-SP is an institution engaged in savings and loans and belongs to the village /kelurahan community which is cultivated and managed by the village / kelurahan community.The purpose of this thesis is to find out the Savings and Loans Implementation of the Savings andLoans Economic Enterprise (UED-SP) of the Cumpun Flower to Increase the Economy of theBanjarGuntung Village Community. The type of research that will be used is sociological research, sausageresearch is research that examines its legal aspects by looking at the applicable legislation and comparing itwith its implementation in the field by means of surveys. The location of the study was carried out at theUED-SP Kembang Serumpun located in Banjar Guntung Village, Kuantan Mudik Subdistrict, KuantanSingingi Regency. The research is descriptive. The data sources used are primary, secondary and tertiarylegal data.The results of the study can be concluded, the factors causing the occurrence of bad credit in theUED-SP Kembang Serumpun that I got consisted of the following: Factors originating from UED-SP(Managers and Authorities), First, Managers were not careful in analyzing debtor credit applications.Secondly, over-financing of debtors needs. Third, Lack of supervision over loans. Next are factors that comefrom internal debtors: First, the customer misuses using credit. Second, the customer is less able to managehis business. Third, the customer has bad intentions. Whereas the settlement of problems for debtors whodefault on UED-SP Kembang Serumpun has never been confiscated and sold on collateral for debtors. Thisis based on the results of the decision of the Village Consultative Meeting. The following is a problemsolving for debtors who default: First, a warning / warning letter is given to the summoning process.Second, Extension of credit period. UED-SP Kembang Serumpun did not conduct an auction against debtorswho made arrears who had been given subpoena twice, this policy was decided based on the VillageConsultation because of certain considerations.